PENGARUH PENGGUNAAN E-TAX TERHADAP KEPATUHAN WAJIB PAJAK (Studi pada Kantor Pelayanan Pajak Pratama Cibitung) - Khatleen Ernita; Paul Eduard Sudjiman (Jurnal Ekonomis, 2021)
This study aims to determine how the influence of the use of E-Tax on taxpayer compliance in Cibitung. Respondents in the study were registered residents at the Cibitung Primary Tax Service Office. The data collection technique of this research is by distributing questionnaires to respondents in accordance with the criteria for determining a sample of 26 questionnaires to each taxpayer who has been registered at the Cibitung Tax Service Office. The sample taken in this study used the Incidental Sampling method, which means determining the sample based on the chance to meet the researcher. The results showed that taxpayer compliance was significantly influenced by the use of e-tax. Which also means that more and more taxpayers understand and use e-tax in submitting all their tax obligations in submitting all their tax needs at the Tax Service Office in Cibitung.